Participer et transformer les territoires - Gwendoline L’Her; Myriam Servières; Daniel Siret (Netcom)
If urban data production and management strategies has generated the smartcities movement, digital technology devices are anchored in territories and modify the ordinary practices of inhabitants. They participate as tools in the urban transformation process. We will more particularly attempt to show to what extent does the introduction of ICT devices in citizen participation moments change the political « dispositif ». As perspective, we will present initiatives, which are inspired by citizen sciences and where « participate by doing » means to produce a common knowledge. This article is a state of art which suggests a reflection on the interactions between inhabitants, techniques, and urban public action using the notion of « citizen as sensor ».